Comparison of methods to determine triple oxygen isotope composition of N2O. (27th September 2015) - Dyckmans, Jens; Lewicka‐Szczebak, Dominika; Szwec, Lars; Langel, Reinhard; Well, Reinhard
<x xml:space="preserve">Abstract</x> Rationale The oxygen isotope anomaly, Δ17O, of N2O and nitrate is useful to elucidate nitrogen oxide dynamics. A comparison of different methods for Δ17O measurement was performed. Methods For Δ17O measurements, N2O was converted into O2 and N2 using microwave‐induced plasma in a quartz or corundum tube reactor, respectively, or conversion was carried out in a gold wire oven. In each case, isotope ratios were measured by isotope ratio mass spectrometry. Results All the tested methods showed acceptable precision (coefficient of variation <2.4 % at 160 nmol N2O) with high sample size but the sample size dependence was lowest when using microwave‐induced plasma in a corundum tube reactor. Conclusions The use of microwave‐induced plasma in a corundum tube yields best results for Δ17O measurement on N2O gas samples. Copyright © 2015 John Wiley & Sons, Ltd.